Measuring ability to assess claims about treatment effects: a latent trait analysis of items from the 'Claim Evaluation Tools' database using Rasch modelling. Issue 5 (25th May 2017) - Austvoll-Dahlgren, Astrid; Guttersrud, Øystein; Nsangi, Allen; Semakula, Daniel; Oxman, Andrew D
Abstract : Background: The Claim Evaluation Tools database contains multiple-choice items for measuring people's ability to apply the key concepts they need to know to be able to assess treatment claims. We assessed items from the database using Rasch analysis to develop an outcome measure to be used in two randomised trials in Uganda. Rasch analysis is a form of psychometric testing relying on Item Response Theory. It is a dynamic way of developing outcome measures that are valid and reliable. Objectives: To assess the validity, reliability and responsiveness of 88 items addressing 22 key concepts using Rasch analysis. Participants: We administrated four sets of multiple-choice items in English to 1114 people in Uganda and Norway, of which 685 were children and 429 were adults (including 171 health professionals). We scored all items dichotomously. We explored summary and individual fit statistics using the RUMM2030 analysis package. We used SPSS to perform distractor analysis. Results: Most items conformed well to the Rasch model, but some items needed revision. Overall, the four item sets had satisfactory reliability. We did not identify significant response dependence between any pairs of items and, overall, the magnitude of multidimensionality in the data was acceptable. The items had a high level of difficulty. Conclusion: Most of the items conformed well to the Rasch model's expectations. Following revision of some items, we concluded that most of the items were suitable for use in an outcome measure for evaluating the ability of children or adults to assess treatment claims.